Tetracycline-Resistant Genes in Escherichia coli from Clinical and Nonclinical Sources in Rivers State, Nigeria - Perewari, Doubra Otis; Otokunefor, Kome; Agbagwa, Obakpororo Ejiro (International Journal of Microbiology, 2022)
Background. Monitoring the occurrence of tetracycline resistance and its determinants in both clinical and nonclinical settings is essential in understanding the role played by continuous usage of this drug in animal husbandry and the withdrawal of this drug from clinical practice. Limited information is available on this from our locale. This study, therefore, set out to explore the occurrence of specific tetracycline-resistant genes in Escherichia coli from clinical and nonclinical sources in Rivers State, Nigeria. Methods. Two hundred clinical and nonclinical samples were analyzed for the presence of E. coli using standard phenotypic and genotypic tests. Susceptibility testing was carried out using the Kirby–Bauer disc diffusion method, and specific tetracycline-resistant genes (tetA, tetB, tetG, and tetM) were assayed. Results. Results showed that stool samples had the highest occurrence of E. coli (39, 78%), and soil had the lowest (13, 26%). Tetracycline resistance was observed in 80.7% of total isolates. The tetA genes were the most commonly occurring (n = 80, 89.9%) detected in confirmed E. coli isolates, and tetG, the least commonly occurring (n = 16,18%) of isolates. The combined presence of tetA-tetM was the highest (n = 14, 15.7%), followed by tetA-tetB (n = 13, 14.8%). Conclusion. The present study reports on the occurrence and distribution of four tetracycline-resistant determinants in E. coli from clinical and nonclinical sources in Rivers State, Nigeria. The high-level occurrence of the most commonly occurring tetracycline gene even in nonclinical isolates could be indicative of a potential reservoir of this resistance. And, this could limit the reintroduction of tetracycline even in combination therapy.